Penguatan Literasi Hukum Dan Spiritualitas Kristiani Bagi Penyandang Disabilitas : Sinergi Gereja Dan Akademisi Di Gereja Kristen Jawa Banjarnegara: Pengabdian - Yosep Heristyo Endro Baruno (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The This community service activity was conducted at the Javanese Christian Church in Banjarnegara with the aim of strengthening legal literacy and Christian spirituality for people with disabilities through synergy between the church and academics. The program was motivated by the still-poor understanding of the law and the limited participation of people with disabilities in church activities. Through a collaborative, participatory approach, this activity combines legal literacy training, spiritual reflection, and community-based mentoring. The training was conducted using workshops, service-learning, and pastoral care methods, involving law and theology lecturers, and church administrators. The evaluation results showed a significant increase in participants' legal knowledge, with an average increase of 37% between pre-test and post-test scores. Furthermore, this activity successfully fostered spiritual awareness, strengthening self-confidence, empathy, and solidarity within the congregation. The synergy between the church and academics also resulted in the development of an inclusive training module and a work plan for the "Learning Inclusive Church." Visible social impacts include increased participation of people with disabilities in church services, the formation of an internal advocacy group, and the emergence of a church commitment to implementing disability-friendly services on an ongoing basis.